Double-sided water-blocking tape and preparation method thereof

By employing a combination structure of polyester film surface layer, substrate layer and water-blocking adhesive layer in the water-blocking tape, and utilizing the composite core-shell structure of superabsorbent microspheres and modified kaolin, the problem of the inability of existing single-sided water-blocking tapes to achieve dual water blocking effect and performance improvement is solved.

CN121361254AActive Publication Date: 2026-01-20YANG ZHOU TENGFEI ELECTRIC CABLE & APPLIANCE MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202511947057.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-23
Publication Date
2026-01-20
Estimated Expiration
2045-12-23

AI Technical Summary

Technical Problem

Existing water-blocking strips are mostly single-sided structures, which cannot achieve dual water-blocking effects, and their performance needs to be improved.

Method used

The structure adopts a combination of polyester film surface layer, substrate layer and water-blocking adhesive layer. The water-blocking adhesive layer is composed of coating adhesive, water-blocking powder, superabsorbent microspheres and nonionic polyurethane thickener. The water absorption performance and stability are improved by composite core-shell structure and modified kaolin.

Benefits of technology

It achieves a dual water-blocking effect, improves water absorption rate and gel strength, enhances salt resistance and thermal stability, and prolongs the working time and effectiveness of the water-blocking tape.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121361254A_ABST
    Figure CN121361254A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of water-blocking tapes, in particular to a double-sided water-blocking tape and a preparation method thereof.The double-sided water-blocking tape comprises a polyester film surface layer, a base material layer and a water-blocking glue layer; the water-blocking adhesive layer is prepared from the following components in percentage by weight: 30 to 45 percent of coating adhesive, 30 to 50 percent of water-blocking powder, 10 to 15 percent of superabsorbent microspheres, 0.5 to 1.5 percent of nonionic polyurethane thickening agent and 0.1 to 0.3 percent of organic silicon defoaming agent. The water-blocking effect of the water-blocking tape is improved by adding the superabsorbent microspheres and the water-blocking powder in a composite synergistic manner, and meanwhile, the polyester film is coated to form the double-sided water-blocking tape, so that factice permeation can be prevented, the water-blocking performance can be ensured, and the water-blocking tape has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of water-blocking tapes, and particularly relates to a double-sided water-blocking tape and a preparation method thereof. BACKGROUND

[0002] The buffer water-blocking tape is also called water-blocking tape, which is suitable for winding the surface of a power cable conductor and insulation to play a water-blocking role. In recent years, China has increased a large amount of financial and material resources in terms of mileage and operation and maintenance of high-voltage cables. However, cable line faults, especially cable faults, have been analyzed to have a water-blocking tape ablation phenomenon, so the performance research on the water-blocking tape is imperative to reduce the occurrence of cable failure performance.

[0003] The water-blocking tape is an effective auxiliary material for reducing cable failure during use of the cable.

[0004] The water-blocking tape in the prior art is mostly coated with a water-absorbing material on one side of a non-woven fabric to obtain a single-sided water-blocking tape, which cannot play a double water-blocking role and the performance needs to be improved. SUMMARY

[0005] The application aims to provide a double-sided water-blocking tape and a preparation method thereof, which are used to solve the above technical problems in the prior art.

[0006] In order to achieve the above-mentioned purpose, the application adopts the following technical scheme: The technical scheme provided by the application is as follows: In a first aspect, the application provides a double-sided water-blocking tape, which comprises a polyester film surface layer, a base material layer and a water-blocking glue layer. The water-blocking glue layer specifically comprises the following components: a coating adhesive 30-45%, water-blocking powder 30-50%, super-absorbent microspheres 10-15%, a non-ionic polyurethane thickening agent 0.5-1.5%, and an organic silicon defoaming agent 0.1-0.3%.

[0007] Preferably, the coating adhesive is an acrylic polymer with a solid content of 35-45% and a viscosity of 2000-5000 mpa.s; the water-blocking powder is low-crosslinking polyacrylic acid sodium salt with a particle size of 250-300 mesh; and the super-absorbent microspheres have a particle size of 150-200 mesh.

[0008] Preferably, the preparation method of the super-absorbent microspheres comprises the following steps: S1: In an N2 atmosphere, acrylamide, acrylic acid, acryloyl morpholine and 3-allyloxy-2-hydroxy-1-propanesulfonic acid sodium were dissolved in water, and after adjusting the pH with a sodium hydroxide solution, mixed with the oil phase obtained by mixing Span 80, dihydroxy stearic acid and white oil, stirred and treated, then added ammonium persulfate (APS), sodium bisulfite (SHS) and N,N'-methylene bisacrylamide (MBA), polymerized to obtain a core polymer emulsion; In the above process, acrylamide, acrylic acid and acryloyl morpholine, 3-allyloxy-2-hydroxy-1-propanesulfonic acid sodium are used as the water phase; white oil, Span 80 and dihydroxy stearic acid are used as the oil phase to form a water-in-oil reverse suspension system, and the water phase undergoes free radical polymerization under the action of the initiator, and the polymerization reaction is limited in the isolated water phase droplets.

[0009] S2: In an N2 atmosphere, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid were added to water, stirred and treated, then MBA and modified kaolin were added, the pH was adjusted with a NaOH solution, and the core polymer emulsion was added dropwise within 30 min, and stirring was continued, then the initiators APS and SHS were added, and stirring and polymerization were carried out, followed by filtration, drying and sieving to obtain superabsorbent microspheres.

[0010] In the above process, the core surface contains a hydrophobic region from acryloyl morpholine and a small number of hydrophilic points from 3-allyloxy-2-hydroxy-1-propanesulfonic acid sodium, as well as physically adsorbed emulsifiers, and the hydrophilic polymer chains grow, anchor and crosslink on the core surface, gradually wrapping the core particles, at the same time, the modified kaolin is also fixed by the crosslinked network and uniformly dispersed in the shell layer; the shell layer can quickly absorb and lock a large amount of water, and the core provides solid mechanical support after the shell layer swells, preventing the microspheres from being crushed or gel blocked under pressure, and maintaining the three-dimensional structure of the swollen body.

[0011] Preferably, in step S1, the concentration of sodium hydroxide is 1 mol / L; the pH value is adjusted to 6-7; the amount ratio of acrylamide, acrylic acid, acryloyl morpholine, 3-allyloxy-2-hydroxy-1-propanesulfonic acid sodium, water, Span 80, dihydroxy stearic acid, white oil, APS, SHS, MBA is 180-360 g:30-60 g:20-40 g:10-20 g:320-640 mL:240-480 g:60-120 g:1-2 kg:0.18-0.36 g:0.06-0.12 g:0.36-0.72 g; the stirring treatment conditions are that the stirring treatment speed is 400-500 rpm and the stirring treatment time is 25-35 min; the mixing temperature of the mixed oil phase is 35-45℃; and the polymerization conditions are that the polymerization temperature is 40-50℃ and the polymerization time is 3.5-4.5 h.

[0012] Preferably, in the step S2, the amount ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, water, MBA, modified kaolin, APS, SHS is 15-30 g:9-18 g:6-12 g:150-300 mL:0.3-0.6 g:3-6 g:22.5-50 mg:7.5-15 mg; the stirring treatment time is 30-40 min; the concentration of NaOH solution is 1 mol / L; the pH value is adjusted to 6-7; the continued stirring treatment conditions are that the stirring speed is 350-450 rpm and the stirring treatment time is 25-35 min; the stirring polymerization conditions are that the stirring speed is 500-700 rpm, the stirring polymerization time is 1.5-2.2 h, and the stirring polymerization temperature is 40-50℃; and the drying temperature is 60-70℃.

[0013] Preferably, the preparation method of the modified kaolin comprises the following steps: The nano-kaolin is dispersed in anhydrous ethanol, and after ultrasonic treatment, 3-(methacryloyloxy)propyltrimethoxysilane (KH-570) solution is added dropwise, acetic acid is used to adjust the pH value, water bath reflux reaction is performed, centrifugation, washing, vacuum drying, grinding are performed, and the modified kaolin is obtained.

[0014] In the above process, the silanol groups generated by the hydrolysis of the silane coupling agent KH-570 and the hydroxyl groups on the surface of the nano-kaolin undergo dehydration condensation reaction, and the silane coupling agent containing double bonds is introduced onto the surface of the nano-kaolin.

[0015] Preferably, the particle size of the modified kaolin is 2-4 μm; the amount ratio of nano-kaolin and anhydrous ethanol is 50-100 g:500-1000 mL; the ultrasonic treatment time is 25-35 min; the concentration of acetic acid is 1 mol / L; the pH value is adjusted to 4-5; the water bath reflux reaction conditions are that the water bath reflux reaction temperature is 65-75℃ and the water bath reflux reaction time is 5.5-6.5 h; the washing method is that the anhydrous ethanol is washed for 3-5 times; and the vacuum drying temperature is 55-65℃.

[0016] Preferably, the preparation method of the KH-570 solution is that 10-20 g of KH-570 is dissolved in a mixture of 200-400 mL of anhydrous ethanol and 50-100 mL of deionized water to obtain the KH-570 solution.

[0017] In a second aspect, the present application also provides a preparation method of the double-sided water-blocking tape, which comprises the following steps: Step (1) substrate selection: selecting polyester non-woven fabric; Step (2) preparing water-blocking glue: mixing coating adhesive, water-blocking powder, superabsorbent microspheres, non-ionic polyurethane thickening agent, and silicone defoaming agent to obtain water-blocking glue; Step (3) is compounded by polyamide hot melt adhesive on one side of polyester film and terylene non-woven fabric, then water-blocking glue roller is coated on the other side of terylene non-woven fabric, dried, slitting, to obtain double-sided water-blocking tape.

[0018] Preferably, in the step (1), the unit area weight of terylene non-woven fabric is 30-40g / m².

[0019] Preferably, in the step (3), the dry base coating amount of double-sided water-blocking tape is 90-110g / m², the unit area weight is 140-170g / m², and the thickness is 0.27-0.33mm; the thickness of polyester film is 13-18μm.

[0020] Preferably, in the step (3), the method of compounding polyester film and terylene non-woven fabric on one side by polyamide hot melt adhesive is as follows: polyamide hot melt adhesive is roller coated on polyester film at 170-190℃, and the cooling chamber is at room temperature; the dry base coating amount of hot melt adhesive is 15-20g / m 2 ; the roller coating line speed is 20-40m / min; and the drying temperature is 120-180℃.

[0021] As described above, due to the adoption of the above technical solutions, the present application has the following advantages: 1. The double-sided water-blocking tape prepared by the present application is suitable for wrapping the conductor and insulating surface of power cable to provide double water-blocking effect, and is used for the outer surface of the core of optical cable and communication cable filled with oil paste, with polyester film inside, which can prevent oil paste from penetrating and ensure water-blocking performance.

[0022] 2. The water-blocking tape prepared by the present application is compounded by adding super-absorbent microspheres and water-blocking powder, the core-shell structure can improve the water absorption rate and gel strength, the dense shell layer can improve the thermal stability of the microspheres itself, the acryloyl morpholine in the core material as a hydrophobic rigid monomer can enhance the network strength and thermal stability of the polymer; the modified kaolin improves the compatibility with the polymer and provides physical crosslinking points, improves the gel strength after water absorption, prevents the loss of microspheres dispersion in water, and maintains a high swelling height; the microspheres continuously swell and increase in size, part of the microspheres directly adhere to each other and aggregate into larger volume flocculation, delaying the rupture and release of the internal core layer polymer, and the water-blocking powder is compounded, which synergistically improves the action time and effect of the water-blocking tape.

[0023] 3. The non-ionic acryloyl morpholine in the water-blocking tape prepared by the present application reduces the overall charge density of the polymer network, weakens the Donnan balance effect that causes the hydrogel to shrink in a salt water environment, and the sulfonic acid group from sodium 3-allyloxy-2-hydroxy-1-propanesulfonate exhibits stronger ion pair dissociation ability than carboxylate group, reduces the complexation with multivalent cations, reduces the charge shielding effect by non-ionic acryloyl morpholine and the strong hydration of sulfonic acid group, and improves the salt resistance of the water-blocking tape. BRIEF DESCRIPTION OF DRAWINGS

[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present application or the prior art, the drawings needed to be used in the embodiments or the prior art description will be briefly introduced. Obviously, the drawings in the following description are only some embodiments of the present application, and other drawings can be obtained by those skilled in the art without creative labor on the basis of these drawings.

[0025] Figure 1 is a mechanical strength histogram of the double-sided water-blocking tape of the present application; Figure 2 is a water absorption performance histogram of the double-sided water-blocking tape of the present application. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present application will be described clearly and completely below in combination with the drawings in the embodiments of the present application. Obviously, the described embodiments are only some embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.

[0027] Some of the substances and sources involved in the following examples and comparative examples are shown in Table 1: Table 1

[0028] Example 1: The present embodiment discloses a preparation method of modified kaolin, comprising the following steps: 75 g of nano-kaolin was dispersed in 750 mL of anhydrous ethanol, and after ultrasonic treatment for 30 min, a kaolin suspension was obtained. Then, 15 g of KH-570 was dissolved in a mixture of 300 mL of anhydrous ethanol and 75 mL of deionized water, and after magnetic stirring for 30 min, it was added dropwise into the kaolin suspension. 1 mol / L acetic acid was used to adjust the pH to 4.5, and the reaction was carried out under reflux at 70°C for 6 h. After centrifugation, the product was washed with anhydrous ethanol 4 times, and then vacuum dried at 60°C. After grinding, the modified kaolin was obtained.

[0029] Example 2: The present embodiment discloses a preparation method of superabsorbent microspheres, comprising the following steps: S1: 270 g of acrylamide, 45 g of acrylic acid, 30 g of acryloylmorpholine and 15 g of 3-allyloxy-2-hydroxy-1-propanesulfonic acid sodium salt were dissolved in 480 mL of water, the pH was adjusted to 6.5 with 1 mol / L sodium hydroxide solution, then the oil phase obtained by mixing 320 g of Span 80 and 90 g of dihydroxystearic acid with 1.5 kg of white oil was dissolved at 40°C, then the mixture was stirred at a speed of 450 rpm for 30 min under N2 atmosphere, then 0.27 g of APS, 0.09 g of SHS and 0.54 g of crosslinking agent MBA were added, and polymerization was carried out at 45°C for 4 h to obtain a core polymer emulsion; S2: 22.5 g of acrylamide, 13.5 g of acrylic acid, 9 g of 2-acrylamide-2-methylpropanesulfonic acid were added to 225 mL of water, stirred for 35 min, then 0.45 g of crosslinking agent MBA and 4.5 g of modified kaolin prepared in Example 1 were added, the pH was adjusted to 6.5 with 1 mol / L NaOH solution, then the core polymer emulsion was added dropwise within 30 min, stirred at a speed of 400 rpm for 30 min under N2 protection, then 33.8 mg of APS and 11.3 mg of SHS were added, and polymerization was carried out at 45°C with stirring at a speed of 600 rpm for 2 h, then filtered, dried at 65°C, and sieved to obtain super water absorption microspheres.

[0030] Example 3: The present embodiment discloses a preparation method of super water absorption microspheres, comprising the following steps: S1: 270 g of acrylamide, 45 g of acrylic acid, 30 g of acryloylmorpholine and 15 g of 3-allyloxy-2-hydroxy-1-propanesulfonic acid sodium salt were dissolved in 480 mL of water, the pH was adjusted to 6.5 with 1 mol / L sodium hydroxide solution, then the oil phase obtained by mixing 320 g of Span 80 and 90 g of dihydroxystearic acid with 1.5 kg of white oil was dissolved at 40°C, then the mixture was stirred at a speed of 450 rpm for 30 min under N2 atmosphere, then 0.27 g of APS, 0.09 g of SHS and 0.54 g of crosslinking agent MBA were added, and polymerization was carried out at 45°C for 4 h to obtain a core polymer emulsion; S2: 22.5 g of acrylamide, 13.5 g of acrylic acid, 9 g of 2-acrylamide-2-methylpropanesulfonic acid were added to 225 mL of water, stirred for 35 min, then 0.45 g of crosslinking agent MBA and 4.5 g of modified kaolin prepared in Example 1 were added, the pH was adjusted to 6.5 with 1 mol / L NaOH solution, then the core polymer emulsion was added dropwise within 30 min, stirred at a speed of 400 rpm for 30 min under N2 protection, then 33.8 mg of APS and 11.3 mg of SHS were added, and polymerization was carried out at 45°C with stirring at a speed of 600 rpm for 2 h, then filtered, dried at 65°C, and sieved to obtain super water absorption microspheres.

[0031] Example 4: The present embodiment discloses a preparation method of superabsorbent microspheres, comprising the following steps: S1: 360 g of acrylamide, 30 g of acrylic acid, 40 g of acryloyl morpholine and 10 g of 3-allyloxy-2-hydroxy-1-propanesulfonic acid sodium salt are dissolved in 640 mL of water, the pH is adjusted to 6 with 1 mol / L sodium hydroxide solution, then mixed with 480 g of Span 80, 60 g of dihydroxy stearic acid and 2 kg of white oil at 35°C to obtain an oil phase, stirred at a speed of 500 rpm for 25 min under N2 atmosphere, then 0.36 g of APS, 0.06 g of SHS and 0.72 g of crosslinking agent MBA are added, and polymerized at 40°C for 4.5 h to obtain a core polymer emulsion; S2: 15 g of acrylamide, 18 g of acrylic acid, 6 g of 2-acrylamide-2-methylpropanesulfonic acid are added to 300 mL of water, stirred for 30 min, then 0.6 g of crosslinking agent MBA and 3 g of modified kaolin prepared in Example 1 are added, the pH is adjusted to 7 with 1 mol / L NaOH solution, then the core polymer emulsion is added dropwise within 30 min, stirred at a speed of 350 rpm for 35 min under N2 protection, then 22.5 mg of initiator APS and 15 mg of SHS are added, and polymerized at 40°C with stirring at a speed of 700 rpm for 1.5 h, filtered, dried at 70°C, and sieved to obtain superabsorbent microspheres.

[0032] Example 5: The present embodiment discloses a preparation method of a double-sided water-blocking tape, comprising the following steps: Step (1) substrate selection: a polyester non-woven fabric with a unit area weight of 35 g / m²; Step (2) preparation of water-blocking glue: a coating adhesive acrylic polymer with a solid content of 40% and a viscosity of 3000 mpa.s 38%, a low-crosslinking polyacrylic acid sodium salt 46%, superabsorbent microspheres prepared in Example 2 14.8%, a non-ionic polyurethane thickening agent 1%, and a silicone defoaming agent 0.2%; Step (3) after the polyester film is compounded with one side of the polyester non-woven fabric through polyamide hot melt adhesive, the water-blocking glue is roll-coated on the other side of the polyester non-woven fabric, the line speed is 30 m / min, and the polyester non-woven fabric is dried at 150°C to obtain a double-sided water-blocking tape.

[0033] The particle size of the low-crosslinking polyacrylic acid sodium salt is 260 mesh; and the particle size of the superabsorbent microspheres is 170 mesh.

[0034] The dry base coating amount of the double-sided water-blocking tape is 100 g / m 2 ; and the thickness of the polyester film is 15 μm.

[0035] Polyester film and one side of the polyester non-woven fabric are compounded by polyamide hot melt adhesive method: at 180℃, polyamide hot melt adhesive is coated on the polyester film, and polyester composite non-woven fabric is obtained after cooling; the dry base coating amount is 17g / m 2 .

[0036] Example 6: The embodiment discloses a preparation method of a double-sided water-blocking tape, comprising the following steps: Step (1) substrate selection: polyester non-woven fabric with a unit area weight of 30g / m 2 ; Step (2) preparation of water-blocking glue: coating adhesive acrylic polymer with a solid content of 45% and a viscosity of 5000mpa.s 35%, low-crosslinking polyacrylic acid sodium salt water-blocking powder 48.5%, superabsorbent microspheres prepared in Example 3 15%, non-ionic polyurethane thickening agent 1.3%, and silicone defoaming agent 0.2%; Step (3) after the polyester film and one side of the polyester non-woven fabric are compounded by polyamide hot melt adhesive, the water-blocking glue is coated on the other side of the polyester non-woven fabric at a linear speed of 20m / min, and the polyester non-woven fabric is dried at 180℃, and then the double-sided water-blocking tape is obtained after slitting.

[0037] The low-crosslinking polyacrylic acid sodium salt has a particle size of 250 meshes, and the superabsorbent microspheres have a particle size of 200 meshes.

[0038] The dry base coating amount of the double-sided water-blocking tape is 90g / m 2 ; and the thickness of the polyester film is 18μm.

[0039] Polyester film and one side of the polyester non-woven fabric are compounded by polyamide hot melt adhesive method: at 190℃, polyamide hot melt adhesive is coated on the polyester film, and polyester composite non-woven fabric is obtained after cooling; the dry base coating amount is 20g / m 2 .

[0040] Example 7: The embodiment discloses a preparation method of a double-sided water-blocking tape, comprising the following steps: Step (1) substrate selection: polyester non-woven fabric with a unit area weight of 40g / m 2 ; Step (2) preparation of water-blocking glue: coating adhesive acrylic polymer with a solid content of 35% and a viscosity of 2000mpa.s 45%, low-crosslinking polyacrylic acid sodium salt water-blocking powder 43.9%, superabsorbent microspheres prepared in Example 4 10%, non-ionic polyurethane thickening agent 0.8%, and silicone defoaming agent 0.3%; Step (3) The polyester film is compounded with one side of the polyester non-woven fabric by polyamide hot melt adhesive, then water-blocking glue roller is coated on the other side of the polyester non-woven fabric, the linear speed is 30 m / min, and drying is carried out at 120 DEG C, and then cutting is carried out to obtain a double-sided water-blocking tape.

[0041] The low cross-linking type polyacrylic acid sodium salt has a particle size of 300 meshes; and the super water-absorbent microsphere has a particle size of 150 meshes.

[0042] The dry basis coating amount of the double-sided water-blocking tape is 110 g / m 2 ; and the thickness of the polyester film is 13 pm.

[0043] The polyester film is compounded with one side of the polyester non-woven fabric by polyamide hot melt adhesive, then water-blocking glue roller is coated on the other side of the polyester non-woven fabric, the linear speed is 30 m / min, and drying is carried out at 120 DEG C, and then cutting is carried out to obtain a double-sided water-blocking tape. 2

[0044] Comparative Example 1 Comparative Example 1 and Example 5 are compared, in the process of preparing the double-sided water-blocking tape, no super water-absorbent microsphere is added in Comparative Example 1, and other conditions are unchanged.

[0045] Comparative Example 2 Comparative Example 2 and Example 5 are compared, in the process of preparing the double-sided water-blocking tape, no S2 is added in preparing the super water-absorbent microsphere in Example 2, and other conditions are unchanged, and the specific steps are as follows: 270 g of acrylamide, 45 g of acrylic acid, 30 g of acryloyl morpholine and 15 g of 3-allyloxy-2-hydroxy-1-propanesulfonic acid sodium are dissolved in 480 mL of water, 1 mol / L sodium hydroxide solution is used to adjust the pH to 6.5, then 320 g of Span 80 and 90 g of dihydroxystearic acid are added to 1.5 kg of white oil to obtain an oil phase, stirring is carried out at 450 rpm for 30 min under N2 atmosphere, then 0.27 g of APS, 0.09 g of SHS and 0.54 g of crosslinking agent MBA are added, and polymerization is carried out at 45 DEG C for 4 h, filtration, drying and grinding are carried out to obtain a super water-absorbent resin powder; the super water-absorbent resin powder is used to replace the super water-absorbent microsphere in an equal amount.

[0046] Comparative Example 3 Comparative Example 3 and Example 5 are compared, in the process of preparing the double-sided water-blocking tape, no acryloyl morpholine is added in preparing the super water-absorbent microsphere in Example 2, and other conditions are unchanged.

[0047] Comparative Example 4 Comparative Example 4 and Example 5 are compared, in the process of preparing the double-sided water-blocking tape, 2-acrylamide-2-methylpropanesulfonic acid is used to replace 3-allyloxy-2-hydroxy-1-propanesulfonic acid sodium in an equal amount in preparing the super water-absorbent microsphere in Example 2, and other conditions are unchanged.​

[0048] Comparative Example 5: Comparative Example 5 is compared with Example 5, in the process of preparing the double-sided water-blocking tape, the superabsorbent microspheres of Example 2 are prepared, and no modified kaolin is added, and other conditions are unchanged.

[0049] Comparative Example 6: Comparative Example 6 is compared with Example 5, in the process of preparing the double-sided water-blocking tape, the superabsorbent microspheres of Example 2 are prepared, and the modified kaolin is completely replaced by unmodified kaolin, and other conditions are unchanged.

[0050] The performance of the double-sided water-blocking tapes prepared in Examples 5-7 and Comparative Examples 1-6 is tested.

[0051] Basic performance test method: The expansion height and expansion rate test is tested by the method in Appendix C of JB / T10259—2014 "Water-blocking tape for cables and optical cables", and 150 mL of water is selected as the reference; the tensile test is tested according to the method in GB / T24218.3—2010 "Textiles - Test methods - Part 3: Determination of tensile strength and elongation at break", and the test environment needs to meet the temperature and humidity requirements in GB / T2941—2006; the water content is tested by the oven method, dried at 105℃ to constant weight; the maximum water absorption rate of the water-blocking tape is tested in 0.1 mol / L sodium chloride solution, and the short-term stability and long-term stability tests are carried out in a heat aging oven, and the test results are shown in Table 2.

[0052] Table 2

[0053] According to Table 2 and from Examples 5-7 and Comparative Examples 1-6, the double-sided water-blocking tape prepared in Example 5 has good mechanical properties, water-blocking performance and stability. As can be seen from the comparison of Comparative Examples 1-4 and Examples 5-7, the double-sided water-blocking tape obtained by adding the superabsorbent microspheres prepared by the application can improve the water-blocking performance and stability, and the performance of the double-sided water-blocking tape obtained by the method of the application is the best, and the effect is not obvious when other methods are used instead; as can be seen from Comparative Examples 5-6 and Examples 5-7, the addition of modified kaolin can improve the performance of the double-sided water-blocking tape.

[0054] The above is only a preferred specific embodiment of the application, but the protection scope of the application is not limited thereto, and any person skilled in the art can make equivalent substitutions or changes within the technical scope disclosed by the application and according to the technical solution and inventive concept of the application, which should be covered within the protection scope of the application.

[0055] The preferred embodiments of the application disclosed above are only to facilitate the elucidation of the application. The preferred embodiments do not describe all the details of the application and limit the application to the specific embodiments. Obviously, many modifications and variations can be made in light of the teachings above. The description is chosen and described in order to provide the best illustration of the application and its practical application to those skilled in the art and to enable those skilled in the art to utilize the application in its best mode. The application is only limited by the claims and their full scope and equivalents.

Claims

1. A double-sided water-blocking tape, characterized by, The double-sided water-blocking tape comprises a polyester film surface layer, a substrate layer and a water-blocking glue layer; the water-blocking glue layer specifically comprises the following components: a coating adhesive 30-45%, water-blocking powder 30-50%, super-absorbent microspheres 10-15%, non-ionic polyurethane thickening agent 0.5-1.5%, silicone antifoam agent 0.1-0.3%; The preparation method of the super-absorbent microspheres comprises the following steps: S1: in an N2 atmosphere, acrylamide, acrylic acid, acryloyl morpholine and 3-allyloxy-2-hydroxy-1-propanesulfonic acid sodium are dissolved in water, the pH is adjusted with a sodium hydroxide solution, then mixed with an oil phase obtained by mixing Span 80, dihydroxy stearic acid and white oil, stirred and treated, then APS, SHS and MBA are added, polymerized to obtain a core polymer emulsion; S2: in an N2 atmosphere, acrylamide, acrylic acid and 2-acrylamide-2-methylpropanesulfonic acid are added to water, stirred and treated, then MBA and modified kaolin are added, the pH is adjusted with a NaOH solution, then the core polymer emulsion is added dropwise within 30 min, continue stirring and treating, then the initiator APS and SHS are added, stirred and polymerized, filtered, dried, sieved to obtain super-absorbent microspheres.

2. The double-sided waterstop band of claim 1, wherein, The coating adhesive is an acrylic polymer with a solid content of 35-45% and a viscosity of 2000-5000 mpa.s; the water-blocking powder is a low-crosslinking type polyacrylic acid sodium salt with a particle size of 250-300 mesh; the super-absorbent microspheres have a particle size of 150-200 mesh.

3. The double-sided waterstop band of claim 1, wherein, In the step S1, the amount ratio of acrylamide, acrylic acid, acryloyl morpholine, 3-allyloxy-2-hydroxy-1-propanesulfonic acid sodium, water, Span 80, dihydroxy stearic acid, white oil, APS, SHS, MBA is 180-360 g:30-60 g:20-40 g:10-20 g:320-640 mL:240-480 g:60-120 g:1-2 kg:0.18-0.36 g:0.06-0.12 g:0.36-0.72 g; the concentration of sodium hydroxide is 1 mol / L; the pH value is adjusted to 6-7; the stirring and treating conditions are that the stirring and treating speed is 400-500 rpm and the stirring and treating time is 25-35 min; the mixing temperature of the obtained oil phase is 35-45℃; the polymerization conditions are that the polymerization temperature is 40-50℃ and the polymerization time is 3.5-4.5 h.

4. The double-sided waterstop band of claim 1, wherein, The use amount ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropane sulfonic acid, water, MBA, modified kaolin, APS and SHS in the step S2 is 15-30 g:9-18 g:6-12 g:150-300 mL:0.3-0.6 g:3-6 g:22.5-50 mg:7.5-15 mg; the stirring treatment time is 30-40 min; the concentration of NaOH solution is 1 mol / L; the pH value is adjusted to 6-7; the continued stirring treatment conditions are that the stirring treatment speed is 350-450 rpm and the stirring treatment time is 25-35 min; the stirring polymerization conditions are that the stirring polymerization speed is 500-700 rpm, the stirring polymerization time is 1.5-2.2 h and the stirring polymerization temperature is 40-50 ℃; and the drying temperature is 60-70 ℃.

5. The double-sided waterstop band of claim 1, wherein, The preparation method of the modified kaolin comprises the following steps: The nano kaolin is dispersed in anhydrous ethanol, ultrasonic treatment is performed, then the KH-570 solution is added dropwise, acetic acid is used to adjust the pH value, water bath reflux reaction is performed, centrifugation, washing, vacuum drying and grinding are performed to obtain the modified kaolin.

6. The double-sided waterstop band of claim 5, wherein, The particle size of the modified kaolin is 2-4 μm; the use amount ratio of nano kaolin and anhydrous ethanol is 50-100 g:500-1000 mL; the ultrasonic treatment time is 25-35 min; the concentration of acetic acid is 1 mol / L; the pH value is adjusted to 4-5; the water bath reflux reaction conditions are that the water bath reflux reaction temperature is 65-75 ℃ and the water bath reflux reaction time is 5.5-6.5 h; the washing method is that the anhydrous ethanol is washed for 3-5 times; the vacuum drying temperature is 55-65 ℃; and the preparation method of the KH-570 solution is that 10-20 g of KH-570 is dissolved in a mixture of 200-400 mL of anhydrous ethanol and 50-100 mL of deionized water to obtain the KH-570 solution.

7. A method of manufacturing a double-sided waterstop according to any one of claims 1-6, characterized in that, The method comprises the following steps: Step (1) substrate selection: selecting polyester non-woven fabric; Step (2) preparing water-blocking glue: mixing coating adhesive, water-blocking powder, superabsorbent microspheres, non-ionic polyurethane thickener and silicone defoaming agent to obtain water-blocking glue; Step (3) compounding polyester film and one side of polyester non-woven fabric through polyamide hot melt adhesive, then roll coating water-blocking glue on the other side of the polyester non-woven fabric, drying, slitting to obtain double-sided water-blocking tape.

8. The method of claim 7, wherein the water-blocking tape is prepared by the steps of: The unit area weight of the polyester non-woven fabric in step (1) is 30-40 g / m 2 The dry base coating amount of the double-side water-blocking tape in step (3) is 90-110 g / m2, the unit area weight is 140-170 g / m2, and the thickness is 0.27-0.33 mm; the thickness of the polyester film is 13-18 μm.

9. The method of claim 7, wherein the water-blocking tape is prepared by the steps of: The step (3) is to compound polyester film with one side of polyester non-woven fabric by polyamide hot melt adhesive: coat polyamide hot melt adhesive on polyester film at 170-190℃, cool in room temperature; dry base coating amount of hot melt adhesive is 15-20g / m 2 ; roll coating line speed is 20-40m / min; drying temperature is 120-180℃.

Citation Information

Patent Citations

  • Thermal foaming microsphere and preparation method thereof

    CN113201090A

  • Water-in-oil type nano-emulsion, nano-emulsion composite response type variable-viscosity acid thickening agent and preparation methods of water-in-oil type nano-emulsion and nano-emulsion composite response type variable-viscosity acid thickening agent

    CN113372485A

  • Water-blocking tape of power cable and preparation method of water-blocking tape

    CN114242317A

  • Ultrahigh-temperature-resistant nano plugging agent for water-based drilling fluid and preparation method of nano plugging agent

    CN118184906A

  • Method and equipment for manufacturing double-sided water-blocking tape

    CN120059257A